The Doors of the Prayer Hall of the Basílica de Nuestra Señora del Pilar in Zaragoza - Ortiz Gutiérrez, Esther (Eikón / Imago, 2024)
The Basílica de Nuestra Señora del Pilar has caught the attention of the academic world on numerous occasions throughout history. Despite a proliferation of studies on the building, many questions are yet to be resolved. Such is the case of the doors leading to the prayer hall of the basilica, barely studied by researchers. The objective of this article is to reclaim the artistic value of this sculptural ensemble, through the review of documentary, bibliographic, and, especially, iconographic sources, to understand its execution and context around the dogma of the Immaculate Conception.